Performance and carcass quality of Nellore and F1 Rubia Gallega × Nellore young bulls supplemented with chromium picolinate - Paulo Sérgio Andrade Moreira; Angelo Polizel Neto; Celina Palhari; Felipe Ferreira Faria; Leonardo Virgilio Gregório Guimarães; André Mendes Jorge (Medicina Veterinária, 2019)
Supplementation with chromium may be an alternative to beef production. The objective was to evaluate the performance and carcass quality of uncastrated Nellore (NEL) and F1 Rubia Gallega × Nellore (RGN) young bulls receiving protein-energy supplementation containing chromium picolinate (CrP). Sixty young bulls (30 NEL and 30 RGN) with an initial weight of 232.40 ± 0.0 kg, average age of 210 days, were distributed in a completely randomized design in a 2 × 2 (genetic groups and supplementation with and without CrP) factorial arrangement. The experimental period was 335 days, including 15 days of adaptation, divided into two stages: post-weaning (210 days) and finishing period (110 days) and slaughtered at 530 days of age. No interaction effect (p>0.05) between genetic group and CrP was detected. During the post-weaning period, the RGN animals showed a higher average daily gain (ADG) than the NEL (0.65 × 0.49 kg/day), while in the finishing stage, ADG was similar (p=0.162) between the groups. Supplementation with CrP elevated (p=0.021) ADG by 50 g/day in the post-weaning stage, but lowered it by 130 g/day in the finishing stage. Genetic group and the use of CrP did not affect (p>0.05) loin-eye area, subcutaneous fat thickness, hot carcass weight, carcass dressing percentage, carcass conformation, or degree of fatness. The RGN young bulls have better performance and higher muscle and bone tissue development rates than the NEL. Supplementation with CrP does not influence the carcass quality, but accelerates muscle development in the post-weaning stage.